2016
DOI: 10.1128/aac.02207-15
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Plasmodium vivax crt-o Is Related to Parasite Stage but Not Ex Vivo Chloroquine Susceptibility

Abstract: Chloroquine (CQ)-resistant Plasmodium vivax is present in most countries where P. vivax infection is endemic, but the underlying molecular mechanisms responsible remain unknown. Increased expression of P. vivax crt-o (pvcrt-o) has been correlated with in vivo CQ resistance in an area with low-grade resistance. We assessed pvcrt-o expression in isolates from Papua (Indonesia), where P. vivax is highly CQ resistant. Ex vivo drug susceptibilities to CQ, amodiaquine, piperaquine, mefloquine, and artesunate were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
1
32
1
Order By: Relevance
“…Comparing findings of the present study to those reported previously for P. falciparum and P. vivax isolates from the Brazilian Amazon [ 46 , 47 ] and Indonesia [ 36 , 48 , 49 ] using pLDH ELISA and SMT assays, Cambodian isolates were found to be less susceptible to MQ and PPQ. However, Cambodian and Brazillian P. vivax isolates were more sensitive to CQ than in Papua Indonesia where P. vivax CQ resistance has emerged.…”
Section: Discussionsupporting
confidence: 77%
“…Comparing findings of the present study to those reported previously for P. falciparum and P. vivax isolates from the Brazilian Amazon [ 46 , 47 ] and Indonesia [ 36 , 48 , 49 ] using pLDH ELISA and SMT assays, Cambodian isolates were found to be less susceptible to MQ and PPQ. However, Cambodian and Brazillian P. vivax isolates were more sensitive to CQ than in Papua Indonesia where P. vivax CQ resistance has emerged.…”
Section: Discussionsupporting
confidence: 77%
“…Histone deacetylase inhibitors accelerated the rate of hypnozoite activation in long-term primary simian hepatocyte cultures, suggesting that histone methylation may maintain hypnozoite dormancy by suppressing transcription (42,43). Finally, P. vivax chloroquine resistance has not been found to correlate with DNA changes in pvcrt but may correlate with the expression of this transporter protein, whose ortholog mediates chloroquine resistance in P. falciparum (44)(45)(46).…”
Section: Discussionmentioning
confidence: 97%
“…In terms of gene transcription, however, parasites from patients with PvCR presented up to 6.1 and 2.4 fold increase in pvcrt-o and pvmdr-1 transcription levels, respectively, compared to the susceptible group [ 26 ]. Caution is needed when attempting to extrapolate the ex vivo biomarkers of resistance to the clinical response, since pvcrt-o transcription was not a primary determinant of ex vivo drug susceptibility [ 77 ]. These previous observations suggest that host-parasite interaction factors, such as nutritional and immune components and clinical severity grading, rather than parasite constitutional factors per se , may be involved in PvCR [ 26 , 27 , 78 ].…”
Section: Discussionmentioning
confidence: 99%